2017
DOI: 10.1186/s13018-017-0613-0
|View full text |Cite
|
Sign up to set email alerts
|

Injectable and compression-resistant low-viscosity polymer/ceramic composite carriers for rhBMP-2 in a rabbit model of posterolateral fusion: a pilot study

Abstract: BackgroundThe challenging biological and mechanical environment of posterolateral fusion (PLF) requires a carrier that spans the transverse processes and resists the compressive forces of the posterior musculature. The less traumatic posterolateral approach enabled by minimally invasive surgical techniques has prompted investigations into alternative rhBMP-2 carriers that are injectable, settable, and compression-resistant. In this pilot study, we investigated injectable low-viscosity (LV) polymer/composite bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In a previous study, local delivery of rhBMP-2 from a PEUR scaffold showed complete bridging of the processes and nearly complete degradation at 8 weeks. 68 While a slowly degrading settable polymer reduces the induction of new bone formation, it may also protect the implant against premature AG resorption and loss of mechanical integrity. The effects of the polymer degradation rate on new bone formation will be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, local delivery of rhBMP-2 from a PEUR scaffold showed complete bridging of the processes and nearly complete degradation at 8 weeks. 68 While a slowly degrading settable polymer reduces the induction of new bone formation, it may also protect the implant against premature AG resorption and loss of mechanical integrity. The effects of the polymer degradation rate on new bone formation will be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…No graft failure was observed in any of the groups throughout the 12 weeks, suggesting that AG extenders exhibited sufficient compression-resistant properties. Previous studies in the spine and mandible demonstrated that an elastic modulus >1 MPa provided compression-resistant properties [ 46 , 47 ]. We previously reported PTKUR-AG and PEUR-allograft moduli of 6.08 MPa and 4.38–9.47 MPa, respectively [ 39 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory of Guelcher and collaborators has pioneered the use of biodegradable PUs in orthopedics and has published an appreciable body of work using biodegradable PU scaffolds in combination with osteogenic material such as nanocrystalline hydroxyapatite (nHA), bioactive glass, calcium phosphates, recombinant human bone morphogenetic protein-2 (rhBMP-2), and bone autograft in a variety of pre-clinical bone defect models. [140][141][142][143][144][145][146][147][148][149][150] Although they have utilized several formulations, their PU chemistry most often comprises lysine triisocyanate (LTI) reacted via hand mixing or mixed injection with a variety of polyols such as a polyester triol synthesized from glycerol, ε-caprolactone, glycolide, and D,L-lactide 141 or thioketal-diol (TKdiol) 140 to form poly(ester urethane) (PEUR) or poly(thioketal urethane) (PTKUR), respectively. The main difference between these two PU formulations is their mode of degradation.…”
Section: Bone Graftmentioning
confidence: 99%
“…While PEUR degrades by hydrolysis and oxidation in vivo, PTKUR degrades only in the presence of ROS‐producing cells. The PEUR, combined with MasterGraft™ (MG; Medtronic) ceramic mixture (85% β‐tricalcium phosphate/15% hydroxyapatite), served as a carrier for rhBMP‐2 in several pre‐clinical models ranging from small to large animals and has been used in femoral condyle plug defects, 141 posterolateral lumbar fusion, 142 and mandibular ridge augmentation 143,145,148 . In a femoral condyle plug defect in sheep, the PEUR‐MG without rhBMP‐2 did not heal as completely after 12–15 months as the ceramic alone or PEUR‐autograft scaffolds 141 .…”
Section: Pre‐clinical Applications Of Biodegradable Pu Scaffoldsmentioning
confidence: 99%